1) 5а + 2b + 7(3b + 4а) = 5a + 2b + 21b + 28a = 33a + 23b
2) 7y + 12(2x + 4y) = 7y + 24x + 48y = 24x + 55y
3) 6х + 2 + 14(2x + 8) = 6x + 2 + 28x + 112 = 34x + 114
4) 5(13х + y) + 2(2x + 3y) = 65x + 5y + 4x + 6y = 69x + 11y
5) 17(2а + 4) + 32а + 31 = 34a + 68 + 32a + 31 = 66a + 99
6) 4(7х + 2) + 18 + 9х = 28x + 8 + 18 + 9x = 37x + 26
Пошаговое объяснение:
Для того, чтобы упростить выражение, мы раскрыли скобки и привели подобные слагаемые.
1) 5а + 2b + 7(3b + 4а) = 5a + 2b + 21b + 28a = 33a + 23b
2) 7y + 12(2x + 4y) = 7y + 24x + 48y = 24x + 55y
3) 6х + 2 + 14(2x + 8) = 6x + 2 + 28x + 112 = 34x + 114
4) 5(13х + y) + 2(2x + 3y) = 65x + 5y + 4x + 6y = 69x + 11y
5) 17(2а + 4) + 32а + 31 = 34a + 68 + 32a + 31 = 66a + 99
6) 4(7х + 2) + 18 + 9х = 28x + 8 + 18 + 9x = 37x + 26
Пошаговое объяснение:
Для того, чтобы упростить выражение, мы раскрыли скобки и привели подобные слагаемые.